Hubungan Antara Pola Asuh Demokratis Orang Tua Dengan Keterampilan Sosial Pada Siswa Di Sekolah Dasar - Dewi, Nurmala; Qohar, Abd.; Ulpa, Eska Prawisudawati; Thahir, Andi (Universitas Islam Negeri Raden Intan Lampung, 2021)
Low social skills make children less able to establish good interactions and choose aggressive actions. The low attitude of social skills is that it is difficult to control oneself well, and it is difficult to empathize and it is difficult to interact with others. Social skills are skills in interacting, communicating, and cooperating between humans and other humans. Social skills are very important for every child to have to form a quality relationship with the environment, because a child who has good social skills can express or communicate ideas or ideas so that others can understand what is being conveyed. The existence of social skills in children cannot be separated from parenting patterns, one of which is democratic parenting. Democratic parenting is parenting that emphasizes the needs of children, but does not hesitate to control them.The subjects used in this study were students in grades V and VI at Madrasah Ibtidaiyah Al Fatah, East Lampung, with a total sample of 50 respondents who were taken using purposive sampling technique. The data collection method in this study used a social skills scale consisting of 26 items ( = 0.853 ) , a democratic parenting style scale consisting of 14 items ( = 0.776 ) . The data analysis technique in this study used the Pearson product moment correlation technique.The results of data analysis obtained a value of rxy = 0.671 with a significant level of 0.000 (p > 0.005), this indicates that there is a positive and significant relationship between students’ social skills and democratic parenting of parents. The effective contribution given by the democratic parenting style variable to the social skills variable is 45.01 %.Keywords: Social Skills, Democratic Parenting, Studentss Primary School.